From giant clumps to clouds – I. The impact of gas fraction evolution on the stability of galactic discs. Issue 1 (14th September 2021) - Renaud, Florent; Romeo, Alessandro B; Agertz, Oscar
ABSTRACT: The morphology of gas-rich disc galaxies at redshift $\sim 1\!-\!3$ is dominated by a few massive clumps. The process of formation or assembly of these clumps and their relation to molecular clouds in contemporary spiral galaxies are still unknown. Using simulations of isolated disc galaxies, we study how the structure of the interstellar medium and the stability regime of the discs change when varying the gas fraction. In all galaxies, the stellar component is the main driver of instabilities. However, the molecular gas plays a non-negligible role in the interclump medium of gas-rich cases, and thus in the assembly of the massive clumps. At scales smaller than a few 100 pc, the Toomre-like disc instabilities are replaced by another regime, especially in the gas-rich galaxies. We find that galaxies at low gas fraction (10 per cent) stand apart from discs with more gas, which all share similar properties in virtually all aspects we explore. For gas fractions below $≈ 20{{\ \rm per\ cent}}$, the clump-scale regime of instabilities disappears, leaving only the large-scale disc-driven regime. Associating the change of gas fraction to the cosmic evolution of galaxies, this transition marks the end of the clumpy phase of disc galaxies, and allows for the onset of spiral structures, as commonly found in the local Universe.